2014
DOI: 10.1051/shsconf/20141201024
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Tourist Satisfaction on Mount Kinabalu, Sabah

Abstract: Abstract. An increase in demand specifically for Mt. Kinabalu climbing activity has seen a significant influx of tourist to the Kinabalu Park. The main purpose of this study is to determine the tourist satisfaction level and to identify issues that might affect tourist satisfaction while participating in mountain climbing activity on Mt. Kinabalu, Sabah. Data collection was conducted using a structured questionnaire around the Kinabalu Park headquarter complex. There were 24 items listed out in the questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…One of the baseline indicators for tourist satisfaction as suggested by the World Tourism Organisation (WTO, 1985) is tourists' satisfaction upon leaving the place they have visited. Although two earlier papers on tourist satisfaction level in Kinabalu Park (Talib et al, 2014;Mereng et al, 2016) have identified that tourists, specifically the mountain climbers, are generally satisfied with their experiences in Kinabalu Park, the dimension of their satisfying experience were not elaborated. Herzberg (1966) proposed that "satisfaction" and "dissatisfaction" are two different dimensions and should be accounted for separately in explaining and understanding tourist satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…One of the baseline indicators for tourist satisfaction as suggested by the World Tourism Organisation (WTO, 1985) is tourists' satisfaction upon leaving the place they have visited. Although two earlier papers on tourist satisfaction level in Kinabalu Park (Talib et al, 2014;Mereng et al, 2016) have identified that tourists, specifically the mountain climbers, are generally satisfied with their experiences in Kinabalu Park, the dimension of their satisfying experience were not elaborated. Herzberg (1966) proposed that "satisfaction" and "dissatisfaction" are two different dimensions and should be accounted for separately in explaining and understanding tourist satisfaction.…”
Section: Introductionmentioning
confidence: 99%